Optically Controlled Electron Transfer in a ReI Complex - Rohwer, Egmont J.; Geng, Yan; Akbarimoosavi, Maryam; Daku, Latévi M. Lawson; Aleveque, Olivier; Levillain, Eric; Hauser, Jürg; Cannizzo, Andrea; Häner, Robert; Decurtins, Silvio; Stanley, Robert J.; Feurer, Thomas; et al. (Chemistry : a European journal, 2021)
Ultrafast optical control of intramolecular charge flow was demonstrated, which paves the way for photocurrent modulation and switching with a highly wavelength‐selective ON/OFF ratio. The system that was explored is a fac‐[Re(CO)3(TTF‐DPPZ)Cl] complex, where TTF‐DPPZ=4’,5’‐bis(propylthio)tetrathiafulvenyl[i]dipyrido[3,2‐a:2’,3’‐c]phenazine. DFT calculations and AC‐Stark spectroscopy confirmed the presence of two distinct optically active charge‐transfer processes, namely a metal‐to‐ligand charge transfer (MLCT) and an intra‐ligand charge transfer (ILCT). Ultrafast transient absorption measurements showed that the ILCT state decays in the ps regime. Upon excitation to the MLCT state, only a long‐lived 3MLCT state was observed after 80 ps. Remarkably, however, the bleaching of the ILCT absorption band remained as a result of the effective inhibition of the HOMO–LUMO transition. Optical control of photoinduced electron transfer via selective excitation wavelength is for the first time achieved by incorporation of a tetrathiafulvalene‐fused dipyrido[3,2‐a:2’,3’‐c]phenazine ligand to a ReI chromophore. Gating of charge flow over multiple charge‐transfer pathways is a prerequisite to success in photodiodes.